IMPACT OF OBESITY AND INSULIN RESISTANCE ON BLOOD PRESSURE VARIABILITY IN YOUNG MILITARY PERSONNEL AND THEIR ROLE IN REDUCED OCCUPATIONAL PERFORMANCE (World Bulletin of Public Health, 2026)
Rising obesity and insulin resistance in young adults threaten longterm cardiovascular health. We examined how these metabolic factors relate to 24-hour blood pressure variability (BPV) and occupational performance in 180 healthy young soldiers (mean age 22 years). Participants underwent clinical assessment (BMI, waist circumference), 24-h ambulatory BP monitoring (ABPM) including mean daytime/nighttime BP, dipping status, morning surge and BP variability indices, and laboratory testing (lipid profile, fasting glucose, insulin for HOMA-IR, HbA1c, cortisol, vitamin D, magnesium, liver enzymes, CBC). We also recorded 12-lead ECG and echocardiography, and collected functional performance data (physical fitness tests, service readiness measures). Overweight/obese subjects (n=60) had significantly higher HOMA-IR and dyslipidemia than controls (all p